Carbonate burial regimes, the Meso-Cenozoic climate, and nannoplankton expansion - Tristan Salles; Laurent Husson; Thran Trung Nguyen; Ana Vila-Concejo; Jonathon Leonard; Ana Paula Da Silva; Jody M. Webster; Fabienne Giraud (Proceedings of the National Academy of Sciences, 2025)
The long-term climate of Earth alternates between warmer and cooler periods, for which atmospheric CO 2 content is often viewed as a primary control. Although silicate weathering feedback governs this long-term equilibrium, the partitioning of carbonate burial between neritic and pelagic environments can influence how rapidly the carbon cycle adjusts to perturbations. The impact of neritic carbonates accumulation on oceanic calcium and alkalinity fluxes, nannoplankton productivity, and carbon reservoirs is overlooked. To investigate this role, we combine plate-tectonic reconstructions with climatic and physiographic simulations and apply a macroecological model to estimate Meso-Cenozoic neritic warm-water carbonate habitats and productivity. We find that only during the Early Cretaceous and Cenozoic did geochemical influxes exceed the carbonate accumulation potential of neritic platforms, while for most of the interval they fell short. These alternating states define two regimes: i) habitability-limited periods, where environmental conditions restrict the development of neritic carbonate factories, and ii) alkalinity-limited periods, where ocean chemistry restricts carbonate precipitation. By alternating between these regimes, neritic platforms modulate the buffering capacity and the timescales (10 3 to 10 5 years) of carbon cycle recovery and regulate the development and productivity of nannoplankton, and therefore the biological pump. This framework highlights the role of shallow-water carbonate systems as important modulators of the Earth’s climate system and pelagic ecosystems.